Enterprise reporting - Havrys, M. O.; Havrys, Olha O.; Havrys, O. M. (National Technical University "Kharkiv Polytechnic Institute", 2024)
"Enterprise Reporting" is one of the basic academic disciplines for the specialty 071 "Accounting and taxation" and involves familiarizing students with both the general principles of the domestic enterprises reporting organization and the methodology of the specific forms’ completion. When studying the discipline, the main attention is paid to financial reporting and its role in the functioning of modern enterprises, but tax and other types of reporting are also considered. This gives students the opportunity to master general approaches to reporting on the activities of enterprises and organizations in Ukraine and foreign countries, which is a relevant and important task today. The main goals of studying the discipline "Reporting of enterprises" are the theoretical and practical training of students in the following directions: familiarizing them with the main definitions, essence and types of reporting, the system of accounting and financial reporting in Ukraine, the principles of reporting organization and its quality characteristics, the order of submission and normative regulation, as well as the methodology of compiling the main forms of financial and tax reporting. These lecture notes are meant to be used by both full-time and part-time Ukrainian and foreign students in the specialty 071 "Accounting and Taxation", who study in English, whose number constantly grows in the Educational and Scientific Institute of Economics, Management and International Business. The full course contains 16 lectures (32 academic hours) and 12 topics.
Звітність підприємств
Keywords: enterprise reporting; lecture notes; financial reporting; balance sheet; income Statement; cash flow statement; net worth statement; tax reporting; конспект лекцій; звітність підприємств